Трехэтапный метод выбора оптимальной методологии управления проектом - Кононенко, Игорь Владимирович; Харазий, Анна Владимировна (Харьковский национальный университет радиоэлектроники, 2014)
The paper proposes a method of selecting an optimal project management methodology, which consists of three stages. The first stage is a questionnaire for the project manager, the latter two are aimed at solving multiobjective optimization problems.
Keywords: управление проектами; критерии оптимизации; трудозатраты; оценка зрелости компании; метод анализа иерархий